EXPLORATION OF HUMAN DEGRADATION AS DEPICTED IN WALL-E 2008 - Faidurrohman, Moh (ELite Journal : International Journal of Education, Language and Literature, 2023)
This paper discusses about the exploration of human degradation depicted in film Wall-E (2008). As humans, human dignity will be better for the society but in this film, humans already loss their dignity which make them become downgrade. The story of Wall-E and Eve will help humans to regain their humanity. This article use representation theory by Michael O’Connor (1985) which symbolic representation in literature. The writer collects the data from watch movie critically and takes notes for the important message that implied on that film. This study will use qualitative method to reveal theme and symbolism from symbolic representation theory ease the writer to analyze key scenes and story events in that film. Aims of this study to reveal kinds of human degradation that happened in that story such as environmental, physical, social, and psychological decline. The film serves as a critique of modern consumer culture and technological dependence, offering a powerful message about the importance of environmental responsibility and human connection.